Exercise and Weight Loss Interventions and miRNA expression in Women with Breast Cancer - Adams, Brian D. (Breast Cancer Res Treat, 2018)
PURPOSE: Obesity and weight gain are associated with comorbidities including a higher risk of tumor recurrence and cancer-related deaths among breast cancer(BC) survivors, however the underlying mechanisms linking obesity and cancer are poorly understood. Given the lack of clinically validated BC biomarkers, obesity and weight loss studies utilize serum biomarkers as intermediary outcomes of tumor recurrence. Studies have indicated microRNAs(miRNA)s are reliable biomarkers for cancer. We hypothesized that miRNA expression is correlated with obesity and weight loss amongst BC survivors. This would yield insight into the biological pathways through which this association occurs, enabling more precise development of therapeutics. PATIENTS AND METHODS: We correlated baseline body mass index(BMI) with serum miRNA expression in 121 BC survivors enrolled in the Hormones and Physical Exercise(HOPE) trial. We then analyzed expression of the 35 most abundant miRNAs from HOPE in a six-month randomized controlled weight loss trial(Lifestyle, Exercise, and Nutrition; LEAN) in 100 BC survivors. Ingenuity Pathway Analysis(IPA) software was used to identify biological pathway targets of the BMI-associated and intervention-responsive miRNAs using predictive biomarkers. RESULTS: Pearson correlations in HOPE identified eight miRNAs associated with BMI, including miR_191–5p(r=−0.22, p=0.016) and miR_122–5p(r=0.25, p=0.0048). In the LEAN validation study, levels of miR_191–5p significantly increased during the six-month intervention(p=0.082). Ingenuity Pathway Analysis identified “Estrogen-mediated S-phase entry”(HOPE p=0.003; LEAN p<0.001) and “Molecular mechanisms of cancer”(HOPE p=0.02; LEAN p<0.001) as the top canonical pathways significantly correlated with BMI-associated and intervention-responsive miRNAs, and contain obesity and cancer relevant genes including the E2F family of transcription factors and CCND1, which have been implicated in sporadic BC. CONCLUSION: While the association between obesity and BC recurrence and mortality has been demonstrated in the literature, mechanisms underlying the link between weight gain and cancer are unclear. Using two independent clinical trials we identified novel miRNAs associative to BMI and weight loss and contribute to the development of cancer. Predictive modeling of miRNA targets identified multiple canonical pathways associated with cancer, highlighting potential mechanisms explaining the link between BMI and cancer.